1963
DOI: 10.2118/568-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Vaporization of Crude Oil by Carbon Dioxide Repressuring

Abstract: The object of this study was to determine if crude oii could be produced successfully by a process of crude oil vaporization using carbon dioxide repressuring. This process appears to have application to highly fractured fcwvnations where the major oil cotitent of the reservoir is contained in the non-fractured porosi~with little associated pertneability. Crude oil was introduced into the windowed cell and carbon dioxide was charged to the ceil at the desired pressure. A vapor space was formed above the oil, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…Although the minimum miscibility pressure (MMP) is a fundamental parameter needed to design an EOR project in a conventional reservoir, there is some question as to MMP’s relevance in unconventional reservoirs because oil recovery mechanisms in tight fractured systems are likely to be very different from those that control recoveries in conventional reservoir floods. Laboratory experiments have demonstrated that enhanced crude oil recoveries from unconventional reservoir rocks exposed to CO 2 were based on the ability of CO 2 to penetrate the rock matrix and to dissolve and mobilize the oil hydrocarbons into the CO 2 phase rather than bulk physical processes (e.g., swelling, lowered viscosity, the physical “sweeping” effect) that are important in conventional CO 2 floods. Laboratory studies have also shown that oil recovered from rock in tight fractured formations is driven primarily by concentration-gradient-driven diffusion of oil hydrocarbons from the interstitial pore spaces in the rock to the surface and into the bulk injected fluid in the fractures. In essence, oil recoveries are likely to depend on the ability of the injected EOR fluids to dissolve high amounts of oil hydrocarbons so that they provide a thermodynamic “pump” to aid diffusion of the oil hydrocarbons from the rock pore spaces into the injected gas-dominated fractures. This solubility-driven mechanism was also supported by laboratory extractions of crude oil from Middle Bakken and Bakken shale rock samples with CO 2 which showed that oil recoveries increased as the exposure pressure increased, regardless of whether the pressure was below, above, or substantially above MMP …”
Section: Introductionmentioning
confidence: 99%
“…Although the minimum miscibility pressure (MMP) is a fundamental parameter needed to design an EOR project in a conventional reservoir, there is some question as to MMP’s relevance in unconventional reservoirs because oil recovery mechanisms in tight fractured systems are likely to be very different from those that control recoveries in conventional reservoir floods. Laboratory experiments have demonstrated that enhanced crude oil recoveries from unconventional reservoir rocks exposed to CO 2 were based on the ability of CO 2 to penetrate the rock matrix and to dissolve and mobilize the oil hydrocarbons into the CO 2 phase rather than bulk physical processes (e.g., swelling, lowered viscosity, the physical “sweeping” effect) that are important in conventional CO 2 floods. Laboratory studies have also shown that oil recovered from rock in tight fractured formations is driven primarily by concentration-gradient-driven diffusion of oil hydrocarbons from the interstitial pore spaces in the rock to the surface and into the bulk injected fluid in the fractures. In essence, oil recoveries are likely to depend on the ability of the injected EOR fluids to dissolve high amounts of oil hydrocarbons so that they provide a thermodynamic “pump” to aid diffusion of the oil hydrocarbons from the rock pore spaces into the injected gas-dominated fractures. This solubility-driven mechanism was also supported by laboratory extractions of crude oil from Middle Bakken and Bakken shale rock samples with CO 2 which showed that oil recoveries increased as the exposure pressure increased, regardless of whether the pressure was below, above, or substantially above MMP …”
Section: Introductionmentioning
confidence: 99%
“…In each test case, the slim tube W is a more conservative estimate than the lower pressure bre,ak of the extraction vs. pressure came (see Table 1 and Figs. [2][3][4][5]. The upper pressure brc.ak was usually the most conservative value of COz-oilW.…”
Section: Resultsmentioning
confidence: 99%
“…This presents an optimum C02 concentration in which any further addition of the C02 will not increase the saturation pressure. 4 Application of Saturation Pressure Profiles to Detect Oil Vaporization in C02-0il Systems SPE 20100 5. The optimum saturation pressure selected for oil vaporization indicates the point at which the swelling of the oil is seized, and the vaporization of the crude oil by C02 is the primary recovery mechanism.…”
Section: Saturation Pressures and Expansion Ratios Behavementioning
confidence: 99%